Evidence for a shared nuclear pore complex architecture that is conserved from the last common eukaryotic ancestor - DeGrasse, Jeffrey A.; Devos, Damien (Molecular & cellular proteomics, 2009)
The nuclear pore complex (NPC) is a macromolecular assembly embedded within the nuclear envelope that mediates bidirectional exchange of material between the nucleus and cytoplasm. Our recent work on the yeast NPC has revealed a simple modularity in its architecture and suggested a common evolutionary origin of the NPC and vesicle coating complexes in a progenitor protocoatomer. However, detailed compositional and structural information is currently only available for vertebrate and yeast NPCs, which are evolutionarily closely related. Hence our understanding of NPC composition in a full evolutionary context is sparse. Moreover despite the ubiquitous nature of the NPC, sequence searches in distant taxa have identified surprisingly few NPC components, suggesting that much of the NPC may not be conserved. Thus, to gain a broad perspective on the origins and evolution of the NPC, we performed proteomics analyses of NPC-containing fractions from a divergent eukaryote (Trypanosoma brucei) and obtained a comprehensive inventory of its nucleoporins. Strikingly trypanosome nucleoporins clearly share with metazoa and yeast their fold type, domain organization, composition, and modularity. Overall these data provide conclusive evidence that the majority of NPC architecture is indeed conserved throughout the Eukaryota and was already established in the last common eukaryotic ancestor. These findings strongly support the hypothesis that NPCs share a common ancestry with vesicle coating complexes and that both were established very early in eukaryotic evolution.